Respuesta :
Answer:
[tex]x1 = -2+\sqrt{19} \\x2 = -2-\sqrt{19}[/tex]
Step-by-step explanation:
[tex]x^{2} +4x=15\\x^{2} +4x-15=0\\(x+2+\sqrt{19} )(x+2-\sqrt{19} )=0\\[/tex]
Answer:
[tex]{ \rm{ {x}^{2} + 4x = 15 }}[/tex]
• arrange the equation into the quadratic format:
[tex]{ \rm{ {x}^{2} + 4x - 15 = 0 }}[/tex]
• let's make it a perfect square:
[tex]{ \rm{ \{{x}^{2} + 4x + {( \frac{4}{2} )}^{2} \} \: - 15 - {( \frac{4}{2} )}^{2} = 0}} \\ \\ { \rm{( {x}^{2} + 4x + 4) - 15 - 4 = 0 }} \\ \\ { \rm{ {(x + 2)}^{2} = 19}} \\ \\ { \rm{x + 2 = \pm \sqrt 19}} \\ \\ { \boxed{ \boxed{ \rm{ \: \: x = 2.36 \: \: and \: \: - 6.36 \: \: }}}}[/tex]